2022
DOI: 10.1155/2022/7360065
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Characteristics and Organic Matter Accumulation of Wufeng-Longmaxi Shales in the Southeast of the Sichuan Basin of South China

Abstract: The Upper Ordovician Wufeng Formation and Lower Silurian Longmaxi Formation black shales are the critical targets for shale gas exploration in the Sichuan Basin of South China. The enrichment of organic matter (OM) in shale is the basis for the generation of large-scale shale gas; however, its controlling factors in Wufeng-Longmaxi shales are still under debate, and few studies have focused on the edge of the Sichuan Basin. Based on the mineral composition, total organic carbon (TOC), and systematic inorganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Geochemical methods were employed to determine the source of quartz in the Dalong Formation shale. Al 2 O 3 and TiO 2 were used as indicators of detrital input. , This study revealed a significant correlation ( r = 0.81) between the Al 2 O 3 and TiO 2 contents in the shale (Figure a), suggesting relatively stable terrigenous detrital input during the sedimentation process. However, it is important to note that the Al 2 O 3 and TiO 2 contents were low, with Al 2 O 3 averaging 5.39% and TiO 2 averaging 0.22%.…”
Section: Discussionmentioning
confidence: 99%
“…Geochemical methods were employed to determine the source of quartz in the Dalong Formation shale. Al 2 O 3 and TiO 2 were used as indicators of detrital input. , This study revealed a significant correlation ( r = 0.81) between the Al 2 O 3 and TiO 2 contents in the shale (Figure a), suggesting relatively stable terrigenous detrital input during the sedimentation process. However, it is important to note that the Al 2 O 3 and TiO 2 contents were low, with Al 2 O 3 averaging 5.39% and TiO 2 averaging 0.22%.…”
Section: Discussionmentioning
confidence: 99%